Rekonstruksi Kelembagaan Politik Pasca- Demo Pembubaran DPR-Tinjauan Atas Krisis Institusional dan Perlawanan Sipil di Tahun 2025 - Hendri Suwarsono (Pusat Riset dan Inovasi Nasional, 2026)
Demonstrations demanding the dissolution of the House of Representatives by 2025 highlight a crisis of public trust and serve as a key moment in Indonesia's political landscape. These protests have not only symbolic significance but also lead to elite repositioning, the temporary dismissal of several members, and the cessation of policy that increased benefits. This study examines how the crisis has prompted political institutional reconstruction and the role of civil society in influencing change. A descriptive qualitative approach was used, including literature studies, analysis of academic literature, official documents, and media reports. The findings indicate that actions by the House of Representatives, such as the rotation of Commission III leadership, member deactivation, and rejection of benefit increases, were primarily reactive to public pressure. The discussion reveals that while these actions reduce crisis escalation, they are cosmetic and do not address structural issues like legislative accountability and budget transparency. In conclusion, the 2025 protests provide an opportunity for civil society to engage politically outside elections, but the institutional changes made are short-term. Fundamental reform can only occur if civil movements remain consistent and if political parties and the government commit to reform.